Education and Socialization on the Utilization of Ulam Raja (Cosmos caudatus) Leaves for the Prevention of Diabetes Mellitus in Percut Village (JURNAL PENGMAS KESTRA (JPK), 2025)
Diabetes mellitus (DM) is a degenerative metabolic disorder with a high prevalence among older adults, reaching 24.0% in the 75–79 age group in 2021 and projected to rise to 24.7% by 2045. The low adherence to conventional antidiabetic therapy highlights the need for alternative approaches, including herbal-based interventions. Cosmos caudatus (Ulam Raja) contains flavonoids, phenolics, and antioxidants with documented antihyperglycemic activity, yet its utilization in the community remains limited. This community service program aimed to enhance the knowledge, awareness, and practical skills of residents in Percut Village regarding the use of Ulam Raja as a preventive measure against DM through structured educational activities. The program began with a preliminary survey, followed by the preparation of educational materials covering DM, clinical symptoms, risk factors, and the role of herbal plants as complementary therapy. A pre-test through an interactive question-and-answer session revealed that participants had low baseline knowledge. During the intervention, participants received information on the benefits of Ulam Raja, DM prevention strategies, and the role of pharmacists as health educators. Post-session evaluation indicated improved understanding, demonstrated by accurate responses in follow-up discussions. Random blood glucose measurements were conducted for all participants, showing that 36.67% had normal values (11 participants), 33.33% were categorized as pre-diabetic (10 participants), and 30% were identified as diabetic (9 participants). Most participants were older adult women (90%). Overall, the program effectively enhanced community health literacy regarding DM and encouraged the utilization of local herbal resources for disease prevention while strengthening the role of pharmacists in community-based health promotion.